1993
DOI: 10.1007/bf03223314
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of EB-weldable molybdenum and Mo-Re alloys

Abstract: The electron-beam weldability, structure, and mechanical behavior of molybdenum and Mo-Re alloys produced via powder metallurgy were characterized by comparison with those produced by ingot metallurgy. By establishing the fabrication and processing for reducing the total oxygen of the starting materials, sound electron-beam welds of the powder metallurgy materials could be obtained. Intergranular embrittlement in the weld metal was improved by heat treatment. Carbon doping and postweld heat treatment were sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 10 publications
(10 reference statements)
0
7
0
Order By: Relevance
“…In addition, the research demonstrates that carbonization and heat treatment after welding can effectively raise the strength of the joint of Mo alloys, which is primarily attributed to an increase of the grain boundary cohesion due to the effective carbon segregation and precipitation. [18]. Morito et al (1998) [19] found that the strength and ductility of a welded joint of Mo alloys obtained through EBW can rise after increasing rhenium (Re) content.…”
Section: Ebwmentioning
confidence: 99%
“…In addition, the research demonstrates that carbonization and heat treatment after welding can effectively raise the strength of the joint of Mo alloys, which is primarily attributed to an increase of the grain boundary cohesion due to the effective carbon segregation and precipitation. [18]. Morito et al (1998) [19] found that the strength and ductility of a welded joint of Mo alloys obtained through EBW can rise after increasing rhenium (Re) content.…”
Section: Ebwmentioning
confidence: 99%
“…In the case of joining, both electron beam welding [39][40][41] and friction welding [41 ] of Mo alloys (Mo, TZM, Mo-Nb) have been performed. The effects of impurity contents and their segregation at grain boundaries upon the properties of joints have been examined.…”
Section: Molybdenum *Tomentioning
confidence: 99%
“…Extremely low solubility of oxygen, nitrogen and carbon 2 , which caused intensive segregation of impurities to grain boundaries or other defects, and the high melting point made the fusion welding of Mo-Re alloys difficult. There were some works emphasizing the application of different joining techniques such as electron beam welding 3 , laser beam welding 4,5 , resistance spot welding 6 and friction welding, but most of the joints revealed poor characteristics due to the formation of porosity or brittle intermetallic compounds. Reducing the oxygen content in the welds and proper welding conditions made it possible to produce sound Mo-Re welds in electron beam welding [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%